Maxillary Interdental Osteotomies Have Low Morbidity for Alveolar Crestal Bone and Adjacent Teeth: A Cone Beam Computed Tomography-Based Study - Rodrigues, Daniel B.; Campos, Paulo S. F.; Wolford, Larry M.; Ignacio, Jaqueline [UNESP]; Goncalves, Joao R. [UNESP] (Elsevier B.V., 2018)
Purpose: Maxillary segmentation involving interdental osteotomies can have an adverse effect on the interdental crestal bone and adjacent teeth. The purpose of the present study was to evaluate the effect of interdental osteotomies on surrounding osseous and dental structures, including adjacent teeth, using cone beam computed tomography (CBCT), in patients who underwent segmental maxillary osteotomies. Patients and Methods: The present retrospective cohort study evaluated interdental osteotomy (IDO) sites between the lateral incisors and canines in patients treated with 3-piece Le Fort I osteotomies. CBCT scans were assessed using Kodac Dental Imaging software at specific intervals: T0 (before surgery), T1 (immediately after surgery), and T2 (a minimum of 11 months after surgery). The statistical analysis using a linear regression model was adjusted to compare the variables at the different intervals. Injury to the dental structures was assessed by radiological evidence of dental damage, the requirement for endodontic treatment, or tooth loss. Results: We evaluated 94 IDO sites in 47 patients in the present study. The mean inter-radicular distance at T0 was 2.5 mm. A statistically significant increase was seen in the inter-radicular distance (between T1 and T0) of 0.72 mm, with a reduction of the alveolar bone crest height (between T2 and T0) of 0.19 mm (P < .001) for the group that underwent IDO. A weak correlation was found for this increase in the inter-radicular distance, with changes in the alveolar crest bone height. The potential complications associated with interdental osteotomies such as iatrogenic damage to the tooth structure, the need for endodontic treatment, and tooth loss were not encountered in any patients. Conclusions: We found very low morbidity for the interdental alveolar crest and the integrity of teeth adjacent to interdental osteotomies for patients who underwent maxillary segmentation between the lateral incisors and canines. (C) 2018 American Association of Oral and Maxillofacial Surgeons